Public Investment Effectiveness in Peru’s educational achievements - Silva Gil, Ronald Nilton (2021)
which points educational achievements is determined by years of schooling, set of school and This research finds to explain if the public investment in education is significant to explain the Peru’s educational achievements. Indeed, the research’s objective is to determine if reading comprehension is explained by executed public investment in education in the period 2007-2016. For this reason, research is based in educational production theory, teacher characteristics, child characteristics, household characteristics and educational inputs that households contribute. Further, it built an econometric model to test the relation between these variables. As a result of this, it is proved executed public investment in education it is not a significant variable to explain changes in educational achievements in Peru. Evidently, it demonstrated educational achievements are further explained by others variables which are not commonly analyzed as educational variables. For instance, the rate of schools in good conditions, level of malnutrition, coverage of drinking water, coverage of electricity, coverage of internet and current expending per student. In conclusion, it means public investment in education should concentrate further their interventions in this kind of variables, not only in schools and teachers but in other variables which speak for existent conditions for studying in households. Another important result is found model which it is possible to determine the necessaries changes in the explain variables to increase the educational achievements. Such as the case of Loreto, which need a reduction of 4.5 percentage point in the malnutrition to increase 1 percentage point in educational achievements.